A Model of Servant Leadership According to Sangahavatthu Principles for School Administrators under Bangkok Metropolitan Administration - Limsakunwanich, Montra; Boonpoo, Somsak; Thitavaddhano, PhramahaYannawat (Journal of Multidisciplinary in Humanities and Social Sciences, 2024)
This article aimed to 1) study the needs and necessities of servant leadership among educational institution administrators under the jurisdiction of Bangkok Metropolitan Administration; 2) develop a servant leadership model based on the 4 principles of Sangahavatthu for educational institution administrators under the jurisdiction of Bangkok Metropolitan Administration; and 3) evaluate the servant leadership model according to the 4 principles of Sangahavatthu for educational institution administrators under Bangkok Metropolitan Administration. It was mixed methods research. There were 3 research steps: step 1 was to study the needs and necessities for servant leadership among educational institution administrators by using a questionnaire on a sample of 370 teachers, and the data were analyzed by using basic statistics, namely, percentage, mean, standard deviation, and the index of essential needs (PNImodified); step 2 was to develop a model by interviewing 10 key-informants and organizing a group discussion with 9 experts. The research tools were an interview form and question guidelines for group discussion. The data were analyzed by using content analysis; and step 3 was to evaluate the model by using an evaluation form for a sample of 205 executives, and the data were analyzed by using basic statistics, namely, percentage, mean, and standard deviation. The results of the study found that: 1. The need for servant leadership among educational institution administrators under the Bangkok Metropolitan Administration overall with an index of essential needs (PNImodified) was between 0.052-0.076; 2. A servant leadership model according to the 4 principles of Sangahavatthu for educational institution administrators under the Bangkok Metropolitan Administration consists of 5 elements; and 3. Evaluation of the servant leadership model according to the 4 principles of Sangahavatthu for educational institution administrators under Bangkok Metropolitan Administration overall, the evaluation results were at the highest level in all 4 areas, ordered from highest to lowest, namely: Usefulness, Correctness, Appropriateness, and Possibility respectively. In summary, the research knowledge is concluded into SASA: S (servant leadership), A (awareness), S (sangahavatthu), and A (application).